Fitness & Sports Medicine - Kölling S; Kellmann M; 2 (Dynamic Media Sales Verlag, 1970)
The present article aims at providing an overview of basic requirements and considerations in the area of psychometric training monitoring in elite sports. Theoretical foundations and practical demands on the selection and implementation of psychometric instruments are summarized and exemplified by the assessment of recovery-stress states. Most importantly, validated and evidence-based questionnaires should be preferred over self-built scales to obtain meaningful data. Additionally, current trends and approaches of individualized data analyses to guide an informed decision are discussed. Further research on the applicability of statistical strategies for psychometric data is required. Digital and automatic processing of the data may reduce participant burden, while control over the algorithm and inferences should be maintained by human beings.In essence, psychometric monitoring of the recovery-stress state may serve as supplement to training and regeneration management, provided that the aims and procedures are made transparent, proportionate and reasonable.KEY WORDS: Sport Psychology, Questionnaire, Regeneration